Research Note: All-trans retinoic acids induce adipogenic differentiation of chicken embryonic fibroblasts and preadipocytes - Kim, Dong-Hwan (Poult Sci, 2020)
Adipocytes store excess energy in the form of lipids, whereas fat accretion contributes to feed efficiency, meat quality, and female reproduction in poultry. As a metabolite of vitamin A, all-trans retinoic acid (atRA) has been shown to have influence over metabolic functions such as lipid and energy homeostasis, as well as adipogenesis. Although atRA has been known to function as a regulating factor in mammalian adipogenesis, the effects of atRA on adipogenesis has not been studied in chickens. In this study, chicken preadipocytes isolated from leg fat tissues at embryonic day (E) 14 and chicken embryonic fibroblasts (CEF) harvested at E5 were cultured. The preadipocytes and CEF in culture with 10% chicken serum were treated with various concentrations (0 μmol, 100 μmol, or 150 μmol) of supplemented atRA for 48 h. In these cells, cytoplasmic lipid droplet accumulation and mRNA expression for adipogenic genes were analyzed by Oil-Red-O staining and quantitative real-time PCR, respectively. Analysis of the relative amount of Oil-Red-O staining (lipid accumulation) revealed that all 3 variables increased in a dose-dependent manner, in response to increasing atRA supplementation. Genes involved in adipocyte differentiation, fatty acid transport, and triacylglycerol synthesis in both E14 preadipocytes and E5 CEF were upregulated by supplementation of atRA. These data demonstrated that atRA alone promoted adipogenesis of embryonic preadipocytes and fibroblasts in vitro, suggesting that atRA has an influential role in multiple stages of adipogenesis in chicken embryos.